Pengaruh BTS Sebagai Brand Ambassador Tokopedia Terhadap Keputusan Pembelian - Savrila Sekar Alifia Wibowo; Abdul Yusuf (Peneliti.net, 2023)
Online shopping trend (Online Shopping) is increasingly widespread among various segments of society. As a result, there are more efforts to provide platforms that facilitate transactions between sellers (E-commerce) and buyers through online marketplaces. Tokopedia is one of the marketplaces that competes with other players in the same field. As part of their marketing strategy, Tokopedia has enlisted the Korean boy group BTS as their digital Brand Ambassador with the aim of winning the competition. This research aims to prove the influence of BTS as the brand ambassador of Tokopedia on purchase decisions. The research uses a sample of 100 Tokopedia users who are fans of BTS and aged over 16 years old. The analysis techniques used are multiple linear regression analysis and classic assumption tests to examine the role of BTS as the brand ambassador of Tokopedia on purchase decisions. The test results show that the use of BTS as the brand ambassador of Tokopedia has an influence on purchase decisions on Tokopedia.